Mice Dually Disrupted for Nod2 and Mincle Manifest Early Bacteriological Control but Late Susceptibility During Mycobacterium tuberculosis Infection - Dubé, Jean-Yves; McIntosh, Fiona; Behr, Marcel A. (Frontiers in Immunology, 2022)
Pattern recognition receptors Mincle and NOD2 have been implicated in mycobacterial immunity. However, knockout (KO) animal infection studies with Mycobacterium tuberculosis (Mtb) have had mild/delayed phenotypes. Given that genetic susceptibility to infectious diseases can be polygenic, we hypothesized that murine double knockout (DKO) of Mincle and Nod2 would result in exacerbation of altered immunity to mycobacterial infection leading to a more extreme phenotype than either KO alone. To test this hypothesis, we monitored bacterial burden, immune responses and survival following in vivo infections with Mtb in DKO mice for comparison to wildtype (WT) and single KOs. Bacterial burden and immune responses were not significantly affected at 3 and 6 weeks after infection in all mutant mice. At later timepoints, Nod2-KO mice had reduced survival compared to wildtype mice, and Mincle-KO survival was intermediate. Unexpectedly, dual disruption had no further effect; rather, DKO mice phenocopied Nod2-KO mice. We observed that Mtb-related death, exclusively in mice with disrupted Nod2, was accompanied by greater pulmonary cell death and distinct large necrotic foci. Therefore, determining how these receptors contribute to mycobacterial resistance will require analysis of immunophenotypes and their consequences on host pathology.